Elucidation Of Indoor Air Microbial Air Quality And Occurrence Of Mycotoxin In Old Building - Hamdan, Anis Syuhada Omar (2025)
Mycotoxins are secondary metabolites released by filamentous fungi and moulds that may negatively impact the building occupant’s health. Most of the building occupants tend to spend their time in an indoor environment, which might be a health risk due to the presence of mycotoxins, by-products of fungi. In addition, older buildings often experience significant issues due to material and physical deterioration, which can lead to the presence of harmful biological contaminants in the occupants' environment. In Malaysia, at this point, there has been limited study on the occurrence of mycotoxins in indoor air, especially in old buildings. The present study investigated and identified the fungi and mycotoxins that occurred in selected old buildings, together with the potential health risks among the building occupants. Two old buildings, the Institute for Medical Research (IMR) and Universiti Sains Malaysia (USM), were selected for this study. There were 18 sampling locations, and each building had nine locations that were identified with the fungus problem and moisture damage. The total number of building occupants who joined the survey using a validated self-administered questionnaire was 49, of which 25 were building occupants from IMR, and 24 were building occupants from the USM building. Results indicated that 17 of the sampling locations in old buildings were observed not to comply with the recommended limit stated by the ICOP IAQ Malaysia DOSH (2010) guideline. Overall, only one location, BS3, complied with the recommended limit of CO2 concentration, humidity percentage, and temperature reading. A total of 333 species were isolated from three types of samples (indoor air, swab, and scrap) and successfully identified using molecular identification.